Empirical properties of an extended CES utility function in representing distributional preferences - Keigo Inukai; Yuta Shimodaira; Kohei Shiozawa (Osaka University, Institute of Social and Economic Research (ISER), 2022)
In previous work, we proposed a method to address mathematical inconvenience by extending the constant elasticity of substitution (CES) utility function in Inukai, Shimodaira, and Shiozawa (2022, ISER DP No.1195). However, the relationships between the extended CES parameters and the external measurements are yet unrevealed. To explore these empirical properties of the extended CES utility function, in this paper we construct an online experiment of Amazon Mechanical Turk workers using a modified dictator game, a public goods game, and a questionnaire. We then compare the parameters of the utility function according to the modified dictator game to behavior in the public goods game and the responses to the questionnaire. This provides evidence that the distribution parameter of the extended CES utility function measures the preference for equality or selfishness. However, we do not find any positive evidence that the substitution parameter measures the preference for efficiency.
Keywords: C91; D63; D64; D90; 330; CES; Distributional preferences; Equality; Efficiency; Amazon Mechanical Turk